(untitled) (Research, Society and Development, 2022)
This article aims to present the blended model of the Pedagogical Proposal of the second segment of EJA implemented at the Samuel Benchimol Municipal Center for Youth and Adult Education and its contributions to the teaching and learning process of students from the municipal public education network. From Manaus/am. This is an exploratory study, with a qualitative approach, using bibliographic and documentary research as methodological support. The results indicate that the blended format contributed satisfactorily to the indicators of approval and permanence of students in the school environment. Thus, it is concluded that these results can be attributed to curricular flexibility, which allows students of the EJA to fulfill 60% of the workload in the modality of distance ds and to study the disciplines by blocks. In this model, the students become the protagonists of the learning process, gaining autonomy and flexibility to define the time and place to study, taking into account their specificities. Thus, it is affirmed that the semi-face-to-face format adopted in CEMEJA fulfills the restorative, equalizer and qualifier functions of the EJA.